Does Islamic Work Ethic influence Affective Commitment with Job Satisfaction as Mediation? Empirical Evidence from Non-Profit Organization - Wahyu Saripudin; Alif Abang (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
The study's objective was to  examine the impact of Islamic Work Ethic on the affective commitment of non-profit organization through job satisfaction as a mediating variable. Research data collection was conducted on 201 employees of non-profit organization in Lombok. The research sample was taken using the purposive sampling technique. The results showed that Islamic Work Ethics has a significant and positive influence on the Job Satisfaction with unstandardized Beta value is 0.292. It strengthens the results of Shafique’s previous research in 2015 that Islamic Work Ethics has a positive influence on the Job Satisfaction of employees. Meanwhile, Islamic Work Ethics significantly affects the Affective Commitment through Job Satisfaction as a mediation variable with unstandardized Beta value is 0.911 (indirect effect). Then, it can be said that there is a partial mediation in this study.